Socio legal studies on family relationship in rural areas in Malaysia: an empirical evidence - Md Hashim, Noraini; Che Soh @ Yusoff, Roslina; Wok, Saodah; Md Said , Muhamad Helmi (2015)
Having a good relationship with each family members are the utmost consideration in the family. This socio legal study will be focusing on family institution itself whereby all family members play pivotal roles in determining the wellbeing of the family. The main objective is to understand the family relationship in terms of legal awareness among family members. Survey was the main method used in this study and will be analyzed using statistical techniques. Semi structured interview has also been conducted in this research. The study shows that most of the rural folks are preferable to the mediation in settling their disputes. The findings of this research are expected to fill in the gap in socio legal literature in Muslim marriages matter and to justify for valid reasons in designing new policy and regulatory framework in dealing with the implementation and enforcement of Islamic Family Law in Malaysia.